Interferon-α2b as a therapy for COVID-19 - Fish, Eleanor N. (Henry Stewart Talks, 2020)
Molecular basis of IFN-α2b use and past indications, Best use of IFN-α2b as therapy, Mode of administration, IFN-α2b use in combination therapy, Next steps in the study